Epidemiological profile of live births: A comparative analysis in a territory marked by geographic mosaics (Research, Society and Development, 2021)
Objective: to analyze the epidemiological profile of live births and to compare between five areas of health planning in the same geographic region. Methods: an epidemiological study, of an ecological, observational, descriptive, quantitative type, elaborated based on the data contained in the Information System on Live Births. The data were processed in the Tab for Windows programs and analyzed in LibreOffice Excel version 5.4. The descriptive results were displayed in absolute and relative frequency and the indicators in proportions according to the mother's AP of residence. Results: 82,780 live birth declarations were analyzed. Most were at term, the weight was adequate, Apgar score between 7 and 10 points in the first and fifth minutes. The mothers were mostly brown, single, with 8 to 11 years of study and aged between 20 to 34. The most frequent type of delivery was cesarean. Final considerations: The evaluation of the epidemiological profile of live births must be part of health services so that strategic actions are directed, in order to intervene in health problems that lead to prematurity, unequal access to prenatal care, and cesarean sections without criteria. Therefore, health services must have a local action plan.